Effect of Special Exercises for the Development of Some Biochemical Variables and the Level of Performance of Diagonal Spike Skill in the Volleyball - Hamida Obaid Abdulamir (Journal of Global Pharma Technology, 2019)
Volleyball is one of the sports activities that need to apply the modern scientific methods through the development of the sport training science, which aims to improve the player's physical and functional abilities through careful planning of training courses for the development of its efficiency in the performance of all requirements for volleyball, The importance of research in the study of some chemical components of blood and the changes obtained by the training using special exercises because of its importance in developing the skill of beating overwhelming in the players the researchers used the experimental method to suit the nature of the problem on the players of the Kufa youth sports club for the season of 2018 (12) players, and was adopted a cohesive method of selection in the selection of the sample, the tests used in the research biochemical tests: measuring variables (cholesterol, sugar, And the test of the skill of beating the overwhelming country, after which the researchers carried out the tribal test, and then the exercise and then the post-test The researchers concluded that the exercises used, which were specialized exercises of the type of skill and complex exercises and exercises. The researchers recommended to emphasize the importance of speed of performance and stress on exercise. Specialization in the skill type especially in the volleyball game, the interest in training the ability to develop the strength of the chemical variables and the level of skill performance of volleyball players, and benefit from the measurement of the activity of enzymes and the proportion of sugar and cholesterol contribute to the processes energy and muscular construction in the training of volleyball players at all levels, and conducting similar research in the use of explosive force training exercises to develop muscle strength in the non-oxygen system and identify the biochemical variables of volleyball players.Keywords: Special exercises, Biochemical variables, Spike, Volleyball.